2021
DOI: 10.1016/j.pcorm.2021.100220
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mRNA vaccination, reactogenicity, work-related absences and the impact on operating room staffing: A cross-sectional study

Abstract: Background The COVID-19 pandemic has caused disruption to healthcare delivery worldwide including in the delivery of surgical services. The introduction of mRNA COVID vaccines and the significant reactogenicity seen with vaccination has caused an unanticipated impact on the operating room workforce via unanticipated paid time off after employee vaccination. Methods A retrospective cross-sectional survey was made available to approximately 33,000 front-line healthcare wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We estimated direct government investment in the vaccination campaign using data provided by the DOHMH ( Table 1 ). 11 , 12 , 13 , 14 , 15 These data included the state and federal funding that came through the DOHMH. Direct costs included the purchase value of vaccine doses over the study period and costs of the vaccination clinic setup; advertisement and outreach; and vaccine transportation, storage, and administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated direct government investment in the vaccination campaign using data provided by the DOHMH ( Table 1 ). 11 , 12 , 13 , 14 , 15 These data included the state and federal funding that came through the DOHMH. Direct costs included the purchase value of vaccine doses over the study period and costs of the vaccination clinic setup; advertisement and outreach; and vaccine transportation, storage, and administration.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect costs of vaccination included workdays lost for visiting vaccination clinics and loss of productivity due to adverse reactions to vaccines. 15 We used published estimates for the prevalence of adverse outcomes after vaccination. 16 , 17 Costs related to workdays lost were estimated using the percentage of vaccinated adults who were employed and per capita personal income of $74 472 for 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Although the primary concern worldwide regarding COVID-19 and worker absenteeism has been related to the impacts of infection and disease, an important consideration in Wide Bay to date has been related to impacts of COVID-19 vaccination and absenteeism. Two studies 19,20 21 For participants receiving BNT162b2, 8% and 21% of participants after their respective first and second dose reported missing work, study or routine duties for the same symptoms 22 , and most participants reported missing one day or less for both BNT162b2 and ChAdOx1-S. 21,22 While our findings are comparable to this, considering the distribution of days missed is important in regional and rural settings, as even modest increases in absence from the healthcare and wider workforce may have a significant impact on service provision compared to urban areas. 20 The strengths of our study include the generation of local data from a regional community, conducted in a pragmatic manner involving many local staff, with a reasonably high uptake facilitated by use of a short survey during the participant's post-vaccination monitoring period.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary concern worldwide regarding COVID‐19 and worker absenteeism has been related to the impacts of infection and disease, an important consideration in Wide Bay to date has been related to impacts of COVID‐19 vaccination and absenteeism. Two studies 19 , 20 in the USA have reported the impact of COVID‐19 vaccination on workplace absenteeism. One study 19 of healthcare personnel (HCP) in Phase one of their COVID‐19 vaccination rollout, found that among ≈4,000 participants (12% response rate) 5% and 20% of participants required an average of 1.7 days and 1.4 days of unanticipated leave post‐first and ‐second dose vaccination respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation